Transmission and prevention of HIV among heterosexual populations in Australia - Persson, A.; Brown, Graham; McDonald, A.; Körner, H. (2014)
© 2014 The Guilford Press. In Australia, unlike much of the rest of the world, HIV transmission through heterosexual contact remains a relatively rare occurrence. In consequence, HIV-prevention efforts have been frmly focused on male-to-male sex as the most frequent source of HIV transmission. There are emerging signs that this epidemiological landscape may be shifting, which raises questions about current and future HIV prevention strategies. Over the past decade, national surveillance data have shown an increase in HIV notifca-tions for which exposure to HIV was attributed to heterosexual contact. This paper offers an epidemiological and sociocultural picture of heterosexual HIV transmission in Australia. We outline recent trends in hetero-sexually acquired HIV and discuss specifc factors that shape transmission and prevention among people at risk of HIV infection through heterosexual contact. To illustrate the contextual dynamics surrounding HIV in this diverse population, we detail two key examples: HIV among people from minority ethnic backgrounds in New South Wales; and overseas-acquired HIV among men in Western Australia. We argue that, despite their differences, there are signifcant commonalities across groups at risk of HIV infection through heterosexual contact, which not only provide opportunities for HIV prevention, but also call for a rethink of the dominant HIV response in Australia.